Plasmin Generation Potential and Recanalization in Acute Ischaemic Stroke; an Observational Cohort Study of Stroke Biobank Samples - Lillicrap, Thomas; Keragala, Charithani B.; Draxler, Dominik F.; Chan, Jilly; Ho, Heidi; Harman, Stevi; Niego, Be'eri; Holliday, Elizabeth; Levi, Christopher R.; Garcia-Esperon, Carlos; Spratt, Neil; Gyawali, Prajwal; et al. (Frontiers in Neurology, 2020)
Rationale: More than half of patients who receive thrombolysis for acute ischaemic stroke fail to recanalize. Elucidating biological factors which predict recanalization could identify therapeutic targets for increasing thrombolysis success. Hypothesis: We hypothesize that individual patient plasmin potential, as measured by in vitro response to recombinant tissue-type plasminogen activator (rt-PA), is a biomarker of rt-PA response, and that patients with greater plasmin response are more likely to recanalize early. Methods: This study will use historical samples from the Barcelona Stroke Thrombolysis Biobank, comprised of 350 pre-thrombolysis plasma samples from ischaemic stroke patients who received serial transcranial-Doppler (TCD) measurements before and after thrombolysis. The plasmin potential of each patient will be measured using the level of plasmin-antiplasmin complex (PAP) generated after in-vitro addition of rt-PA. Levels of antiplasmin, plasminogen, t-PA activity and PAI-1 activity will also be determined. Association between plasmin potential variables and time to recanalization (assessed on serial TCD using the thrombolysis in brain ischemia (TIBI) score) will be assessed using Cox proportional hazards models, adjusted for potential confounders. Outcomes: The primary outcome will be time to recanalization detected by TCD (defined as TIBI≥4). Secondary outcomes will be recanalization within 6-hours and recanalization and/or haemorrhagic transformation at 24-hours. This analysis will utilise an expanded cohort including approximately 120 patients from the Targeting Optimal Thrombolysis Outcomes (TOTO) study. Discussion: If association between proteolytic response to rt-PA and recanalization is confirmed, future clinical treatment may customise thrombolytic therapy to maximise outcomes and minimise adverse effects for individual patients.